SUBVERSIVE FEMALE AGING IN MUNSHI PREMCHAND’S “BUDHI KAKI (THE OLD AUNTY)” - Singh, Sudiksha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The paper aims to dig beneath the contemporary apparent treatment met with female characters who have descended the peak time of their life i.e. teenage, adult, marriage and motherhood (post-menopausal phase of life) and stay at the periphery of the family and societal space and that the centre is occupied by those section of females who can voice out opinions, demand rights and protests against those who sideline them through careful study of Munshi Premchand’s The Old Aunt. The paper explores the common defence strategies that includeincludees denial (the refusal to accept the upsetting reality), displacement (the directing of anger toward people or things that feel unthreatening) and sublimation (and distracting of one’s thoughts by engaging in physical or entertainment activity) and analyze the fissures and nuances present in the contemporary feminist studies that talk about power and equality to be shared between male and female and fails to actually acknowledge the violence and trauma inflicted to the females and which goes unnoticed as they find no seat but marginalized positions and find no recognition or place.